Motivación y desempeño laboral, en la subgerencia regional de supervisión y control de obras del Gobierno Regional de Loreto, 2023 - Mori Lanchi, Leydi Stefani (2023)
The main objective of this thesis is to investigate whether there is a relationship between the motivation and work performance of the collaborators oh the Regional Sub management of Supervision and Control of works of the Regional Government of Loreto, 2023. For this, the quantitative approach was used. Type of correlational descriptive method. Pearson correlation coefficients are calculated using the information obtained from the surveys collect to evaluate the relationship between variables based on the predictable behavior of the sample or population. Once the evidence is found, we can affirm that the previously stated hypothesis is correct. A relevant significant correlation is observed between motivation and work performance in the collaborator of the Regional Sub management of Supervision and Control of Works, 2023.